Problem-based science learning in elementary schools: A bibliometric analysis - Anenggar Dewi Puspita; Ika Maryani; Hanum Hanifa Sukma (Journal of Education and Learning (EduLearn), 2023)
This study aims to identify publication trends and recommendations for problem-based science learning research in elementary schools. We used a mixed-methods research design in which descriptive, qualitative, and bibliometric analyses were used to look at the data. We selected the sample by using the purposive sampling technique. Secondary data contains Sinta-indexed research articles published in the Google Scholar database. Data were analyzed using content analysis and the VOS-Viewer. The results of the analysis show that between 2017 and 2021, 98 articles have been published with the keywords [problem-based learning] and [IPA or science learning] in national and international journals with research settings in Indonesia. Most publications occurred in 2020. The keywords that appear the most in the published articles obtained are [problem-based learning], [learning outcomes], [critical thinking skills], and [science learning]. The keyword [Tri Hita Karana], or three causes of well-being, appears, but with weak nodes. These keywords appear in many publications whose research settings are in Bali because they are ethnoscientific findings from that area. Weak nodes have several conjectures, namely that this theme has been researched to saturate or that research on this theme is still rarely carried out. This research contributes ideas for future research involving the theme of problem-based learning in science.